ANALISIS UNTUK MENGUKUR KINERJA KEUANGAN BANK PADA PD. BPR BKK KARANGMALANG SRAGEN - ., SARSITI (Universitas Surakarta, 2012)
Bank performance can be measured in terms of performance management as a business manager and in terms of its financial performance can be seen from its financial statements. To determine the financial performance of a bank, by analyzing the financial statements of banks consisting of a balance sheet and income statement, using the liquidity ratio, solvency, and profitability ratios. Data analysis methods used by the author to analyze quantitative data using liquidity ratios, profitability ratios and the ratio solviabilitas. From the analysis of the liquidity ratio Quick ratio consisting of 109.47% over the past year concluded that Quick ratio â¥ 100% , so it is included in a healthy predicate, Loan to Deposit Ratio (LDR) ratio was 101.56% for the year concluded that the LDR â¤ 110%, so the predicate is included in a healthy, Loan to Assets Ratio ratio 82.57% a year, so it is included in a healthy predicate. The results of the analysis of the solvency ratio by using the Capital Adequacy Ratio (CAR) of 9.60%, it was concluded that the CAR â¥ 8 %, so the ratio of bank solvency considered healthy. The results of the analysis of the profitability ratio which consists of Return On Assets (ROA) ratio is 4.09% for the year, so the predicate is included in a healthy, Operating Expenses/Operating Income (BO/PO) ratio was 80.56% for the year, so the predicate is included in the healthy, Gross Profit Margin ratio was 24.12% for the year, so the predicate is included in the healthy, and the net profit margin ratio was 119.21% for the year, so it is included in a healthy predicate. Keywords;Â Â Â Â Â Â Â analysis of liquidity ratios, solvency ratios, profitability ratios.